Psychopathology and Identity: Stigma in people diagnosed with mental disorders - Huerta Muñoz, Laura (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2017)
Science in electronic and printed media allows the dissemination of knowledge among the various sectors of society, making scientific knowledge a stock of social knowledge. This stock of social knowledge can act as a typification or "recipe" for everyday life, and in the case of psychiatric and psychological knowledge, diagnoses of "mental illness" (psychopathology) can serve as a prescription both for behavior and for the definition of identity. Exploring the relationship between knowledge about mental disorders and the construction of identities highlights processes of social estrangement, stigmatization and negative definition of identity.